Penggunaan Letter C pada Pelaksanaan Pendaftaran Tanah Secara Sporadik di Daerah - Arrizal, Nizam Zakka; Jescia Dea Mahesty; Rachel Defrans Saputri (Vonis, 2025)
A land title certificate is a document that indicates ownership or control over land. Therefore, the government requires land registration throughout Indonesia so that each landowner receives legal guarantees and protection for their land ownership. One type of initial land registration is sporadic land registration, which is the first registration of one or more land registration objects within a village/sub-district, either individually or collectively. Based on this background, the author wishes to examine the use of Letter C in sporadic land registration in Regency. The research method used is empirical juridical, looking at social phenomena related to law in legislative practice in Indonesia. The empirical juridical approach examines how normative provisions are actually realized in society. The results of the study show that Letter C is still used today as an absolute requirement for sporadic land registration